Eksistensi Kegiatan Forum Keagamaan dalam Meningkatkan Pemahaman Masyarakat Pentingnya Melaksanakan Sholat - Aisyah Rahmadani; Solfema Solfema; Lili Dasa Putri (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
People who still do not know the importance of carrying out prayers, this is the lack of public knowledge about religion. Religious forums that help people can add a little more in-depth knowledge about religion. This article discusses the meaning of religious forums and the purpose of activities, the importance of carrying out prayers. This article also discusses the impact of religious forums on public understanding, the role of ustaz speakers in forums, and the challenges faced during the forum. Qualitative methods are used to examine the implementation of religious forum activities and their impact on public understanding of the importance of carrying out prayers.